Spatial trypanosomosis management: From data - layers to decision making - Hendrickx, G.; Rocque, S. de la; Reid, Robin S.; Wint, W. (Elsevier, 2001)
The use of geographical information systems (GIS) in the management of African animal trypanosomosis in sub-Saharan Africa offers potential in assisting decisions on allocation of resources, prioritization of control areas, and planning and management of field operations. Here, Guy Hendrickx and colleagues review approaches being used to develop reliable data layers and to incorporate these data into GIS models. They argue that techniques should be further refined to produce more-detailed data layers and to include a dynamic element. a problem rarely addressed until now.